Accessibility Analysis of Ecuadorian University Web sites - Chiriboga Casanova, Washington (2024)
The article addresses the navigation difficulties encountered on the web pages of Ecuadorian universities about accessibility. The aim is to determine the extent to which the WCAG 2.1 guidelines applied in these universities. Of the 61 web pages analyzed, only 11 featured a button for visual adjustments. Utilizing TAW (Web Accessibility Test) and  dispersion analysis, it was found that most universities exhibit up to 26.8 errors in the 'Perceivable' principle, 46.8 errors in the 'Operable' principle, 9.4 errors in the 'Understandable' principle, and 9.4 errors in the 'Robust' principle. When using the Markup Validation Service, as many as 80 markup errors were discovered. Similarly, with the CSS Validation Service, up to 143 errors were identified on the web pages. These findings enable web developers to better target their improvements, considering accessibility guidelines.